2016
DOI: 10.18051/univmed.2015.v34.177-186
|View full text |Cite
|
Sign up to set email alerts
|

Honey improves lipid profile of diet-induced hypercholesterolemic rats

Abstract: BACKGROUNDCoronary heart disease (CHD) is a major cause of morbidity and mortality throughout the world, including Indonesia. One of the risk factors for CHD is hypercholesterolemia. One of the natural products that has been developed for the treatment of hypercholesterolemia is honey. Honey contains fructooligosaccharides, various vitamins, minerals, and enzymes which are supposedly able to lower blood cholesterol levels. This research aimed to study the influence of honey on the levels of blood total cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…24 In this study, the rats that underwent diet change coupled with TH supplementation were also recorded to have the lowest total cholesterol and triglyceride levels when compared to the controls. These findings are consistent with Nurmasitoh et al 25 that documented reduction in total cholesterol, triglyceride and LDL-c levels in dietinduced hypercholesterolaemic rats following treatment Kapok Tree honey for seven days. The effect of honey on lipid metabolism was further reinforced by Bezerra et al 26 whereby rats fed with honey from stingless bees (Malícia honey) showed lower food consumption and decreased total cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…24 In this study, the rats that underwent diet change coupled with TH supplementation were also recorded to have the lowest total cholesterol and triglyceride levels when compared to the controls. These findings are consistent with Nurmasitoh et al 25 that documented reduction in total cholesterol, triglyceride and LDL-c levels in dietinduced hypercholesterolaemic rats following treatment Kapok Tree honey for seven days. The effect of honey on lipid metabolism was further reinforced by Bezerra et al 26 whereby rats fed with honey from stingless bees (Malícia honey) showed lower food consumption and decreased total cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…The study also reported that in contrast with HFD-fed rats, honey-fed rats showed enhanced growth of intestinal villi, and no pathology in the rodents’ abdominal viscera, suggesting a potential nutritional benefit of honey as a substitute for refined sugars. 138 Similarly, a short-duration study by Nurmasitoh and Pramaningtyas 128 reported that 0.8 mL honey supplementation per day could reduce the triglyceride, total cholesterol, and LDL serum levels in HFD rats after 15 days ( p < 0.05).…”
Section: Evidence That Honey Has the Potential To Control Obesity Obe...mentioning
confidence: 97%